PERSEPSI CIVITAS AKADEMIKA TERHADAP KESETARAAN GENDER DAN KEPEMIMPINAN PEREMPUAN DI IAIN PADANGSIDIMPUAN - Eka Sustri Harida (Institut Agama Islam Negeri Padangsidimpuan, 2015)
This research was based on misconception or misunderstanding on the concept of gender and the less acceptance on the female’s leadership in State Institute for Islamic Studies (IAIN) Padangsidimpuan. The aims of this research are to describe the perception of civitas academic on gender equality and on women’s leadership in IAIN Padangsidimpuan. The method has been used in this research was qualitiative research by using observation, questionnairesm and interviews. The informants of this research was 48 students and 40 persons from lecturers and others. Data were analyzed through grouping, verifying, interpreting, and taking conclusion. The result of this studying shown that all civitas acedemics IAIN Padangsidimpuan was known enough about the gender equality and also felt welcome to the female leader. From 100% of informants of this research, 75,34% civitas academics knew about or familiar with the equality of gender and also 78,60% welcome to the female leadership. Thus, it can be stated that the concepts of gender equality was understood enough and being applied in IAIN Padangsidimpuan, it was proved by appreciating and accepting the leadership from women in IAIN Padangsidimpuan